Implementation of the deep learning approach in akidah akhlak instruction for strengthening islamic social awareness values among students of mi nurul huda raji, demak - Anzar Aquil; Maria Nurul Qoyyimah; Aliwan; Santi Ratnawati; Diemas Nur Falahur Rozaq; Kamalun Ni’am; Triana Hermawati (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This study aims to describe the implementation of the deep learning approach in Akidah Akhlak instruction to strengthen Islamic social awareness values among students at MI Nurul Huda Raji, Demak. The background of this research is based on the fact that some students still demonstrate inconsistent social behavior that does not fully reflect Islamic moral values in their daily lives. This research employed a descriptive qualitative approach, with data collected through observations, in-depth interviews, and documentation. Data analysis was carried out through data reduction, data display, and conclusion drawing, with triangulation applied to enhance the validity of the findings. The results indicate that Akidah Akhlak teachers implemented deep learning strategies through integrative, reflective, contextual, and experiential approaches in the learning process. The impact of the learning is reflected in students’ improved Islamic social behavior, such as empathy, trustworthiness, cooperation, and active participation in religious and social activities within the school environment. Supporting factors include teachers’ exemplary conduct, the school’s religious culture, and parental involvement, while inhibiting factors relate to limited instructional time and diverse student characteristics. The study concludes that the deep learning approach is effective in sustainably strengthening students’ Islamic social awareness when integrated with consistent habituation and a conducive Islamic learning environment.